Highly dispersed Fe3+-Al2O3 for the Fenton-like oxidation of phenol in a continuous up-flow fixed bed reactor: enhancing catalyst stability through operating conditions - Di Luca, Carla (2018)
A highly dispersed Fe3+-Al2O3 catalyst (6 wt% Fe) was used for the catalytic wet hydrogen peroxide oxidation of phenol (1 g/L) in an up-flow fixed bed reactor (UFBR) under continuous operation. To enhance catalytic performance, three simple synthesis strategies were combined: two-stage impregnation of iron citrate, acid washing with CH3COOH and thermal treatment at 900 °C. Solid samples were characterized in depth by several techniques: N2 Physisorption, XRD, SEM–EDAX, TEM, TGA, PZC, TPD of pyridine, XPS and Mössbauer. Peroxidation experiments were performed in an UFBR over a wide range of operating parameters in order to evaluate their influence on phenol mineralization and catalyst stability. Under selected operating condition (T = 90 °C, Wcat = 20 g, QL = 1.2 mL/min and [H2O2]:[Phenol] = 16.8), complete phenol conversion and remarkable TOC reduction of 90% were achieved, with a high H2O2 consumption efficiency (η = 76%) and low Fe leaching (< 3 mg/L). After 70 h of usage at different steady state conditions, the catalyst retained high mineralization levels (XTOC> 70%) but the cumulative iron loss was calculated to be c.a. 20% of the initial Fe loaded in the UFBR. The catalyst was susceptible to leaching due to the accumulation of complexing intermediates such as carboxylic acids. However, acceptable iron leaching values (< 10 mg/L) were achieved when the reactor operating conditions were properly set (55% < XTOC> 80%). The presence of chelating by-products favored also the Fe redistribution inside the catalyst pellets. Nevertheless, catalyst decay in the long-term operation was mainly due to the occurrence and permanence of chelating organic acids. This process was specially promoted by the amphoteric character of the alumina-based catalyst. However, adsorbed species were promptly eliminated by calcination at 500 °C, recovering steady state conversion profiles.